2021
DOI: 10.3389/fonc.2021.766672
|View full text |Cite
|
Sign up to set email alerts
|

Are the Derived Indexes of Peripheral Whole Blood Cell Counts (NLR, PLR, LMR/MLR) Clinically Significant Prognostic Biomarkers in Multiple Myeloma? A Systematic Review And Meta-Analysis

Abstract: BackgroundMultiple myeloma (MM) is an incurable malignant plasma cell tumor. Whole blood cell count (WBCC) derived indexes are widely used as a predictive biomarker for various types of solid and hematological malignant tumors. Our study is to evaluate its effectiveness in MM by meta-analysis.MethodsRelevant literatures were retrieved from PubMed, Embase and Web of Science databases according to PRISMA guideline. All relevant parameters were extracted and combined for statistical analysis.ResultsNineteen studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have investigated the application of various inflammatory factors as prognostic indices in patients with (12) suggested that a high NLR was an adverse prognostic factor; however, no consensus was reported on its cut-off value (8)(9)(10)(11)(12). These cut-off values ranged from 2 to 3.1 (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have investigated the application of various inflammatory factors as prognostic indices in patients with (12) suggested that a high NLR was an adverse prognostic factor; however, no consensus was reported on its cut-off value (8)(9)(10)(11)(12). These cut-off values ranged from 2 to 3.1 (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory factors include the platelet count (PLT), the neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR), the monocyte-to-lymphocyte ratio (MLR) and C-reactive protein (CRP) levels. Previous studies, such as those of Zhang et al (8), Liu et al (9), Kim et al (10), Szudy-Szczyrek et al (11) and Zuo et al (12) suggested that a high NLR was an adverse prognostic factor. However, no consensus has yet been reached on the cut-off value used for the diagnosis of MM.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations